3D-CT craniofacial morphometry among Malay down syndrome and normal subjects in Hospital Universiti Sains Malaysia - Al-Shammari, Haider Ali Hasan (2018)
This is the first three-dimensional computed tomography (3D-CT) study, as far as the author is aware, of the craniofacial morphology of Malay Down Syndrome (DS) subjects. This information is intended to increase understanding of the DS quantitative phenotypic features in order to improve the strategies required with the management of these patients. To study the size of the craniofacial structure which include linear and angular measurements in Malay DS subjects and to compare them with normal subjects. Additionally, sexual dimorphism and age differences of both the DS and normal subjects were also investigated. This is a cross sectional 3D-CT study on 240 Malays (Normal = 180, DS = 60) aged between 0 to 35 years old. The initial 2D formats were then reconstructed into 3D utilising Mimics V17.0 software. Linear and angular dimensions of craniofacial structures were measured for each subject using consistent landmark definitions. Comparisons were made between DS and normal subjects, between the males and females and among selected age groups. The selected ages are children (0 to 6 years), pre-adolescents (7 to 12 years), adolescents (13 to 20 years) and adults (21 to 35 years). High reliability of the examiner in carrying out the measurements was detected with ICC values in the range of 0.8 to 1. Generally, each craniofacial region showed unique growth pattern as observed from infancy to adulthood. Most of craniofacial measurements in DS subjects showed smaller values than normal from infancy to adulthood. Sexual This is the first three-dimensional computed tomography (3D-CT) study, as far as the author is aware, of the craniofacial morphology of Malay Down Syndrome (DS) subjects. This information is intended to increase understanding of the DS quantitative phenotypic features in order to improve the strategies required with the management of these patients. To study the size of the craniofacial structure which include linear and angular measurements in Malay DS subjects and to compare them with normal subjects. Additionally, sexual dimorphism and age differences of both the DS and normal subjects were also investigated. This is a cross sectional 3D-CT study on 240 Malays (Normal = 180, DS = 60) aged between 0 to 35 years old. The initial 2D formats were then reconstructed into 3D utilising Mimics V17.0 software. Linear and angular dimensions of craniofacial structures were measured for each subject using consistent landmark definitions. Comparisons were made between DS and normal subjects, between the males and females and among selected age groups. The selected ages are children (0 to 6 years), pre-adolescents (7 to 12 years), adolescents (13 to 20 years) and adults (21 to 35 years). High reliability of the examiner in carrying out the measurements was detected with ICC values in the range of 0.8 to 1. Generally, each craniofacial region showed unique growth pattern as observed from infancy to adulthood. Most of craniofacial measurements in DS subjects showed smaller values than normal from infancy to adulthood. Sexual dimorphism was observed for linear and angular variables in both DS and normal subjects. The number of variables that showed sexual dimorphism increased from infancy to adulthood. Differences in size between males and females were not obvious during infancy as only a few variables showed significant differences. During preadolescent and adolescent stages, only some of the variables showed significant size differences between the sexes. Sexual dimorphism in the craniofacial region was most evident during adulthood with more variables displaying significant differences between the sexes. The majority of the craniofacial variables increased in size significantly from birth to 35 years of age in both DS and normal subjects. This study provides comprehensive description of the craniofacial dimensions of Malay DS subjects. This study has generated craniofacial reference data for DS and some additional normal data. These reference data is hoped to facilitate management of Malay DS subjects. Moreover, these information could also help maxillofacial, orthognathic, plastic and reconstructive surgeons, orthodontists, medico-legal experts and forensic scientists to perform objective and quantitative management, decide treatment strategies and assessment of treatment outcome. In addition, the size of craniofacial structures showed sexual dimorphism at most age categories. Gender consideration should be taken into account in clinical assessment and procedures which may affect the craniofacial complex. Furthermore, quantification based on 3D data provides new insights into craniofacial growth changes and morphology compared with conventional 2D approaches.